Synthesis Of Molecular Imprinting Polymers In Microemulsion For The Removal Of Malachite Green From Water - Showkat, Ahmad Bhawani; Amelia Laccy, Jeffrey Kimura (EM International, 2018)
Molecular imprinting polymers for Malachite Green (MG) were synthesized by microemulsion polymerization method. In this research microemulsion (Water+CTAB+Butanol+Hexane, 8G: 8G: 25mL: 160mL) was used as a solvent medium for polymerization. This polymerization method used Malachite Green (MG) as a template, Acrylic acid (AA) as a monomer,Diviniylbenzene (DVB) as a cross-linker and Azobisisobutyronitrile (AIBN) as an initiator.The synthesized polymers were characterized by using FTIR and SEM. The batch binding process was used to evaluate the rebinding efficiency of imprinted polymers. The removal efficiency of selected imprinted polymer (MIP-R2) was about 85% in Lake Water. The competivity binding test reveals that the MIP-R2 is highly selective towards the MG with the Kd (distribution ratio) of 1.700.